Influenza vaccine effectiveness in Australia: results from the Australian Sentinel Practices Research Network. Issue 2 (21st July 2014) - Sullivan, Sheena G; Chilver, Monique B‐N; Higgins, Geoff; Cheng, Allen C; Stocks, Nigel P
Abstract: Objective: To estimate influenza vaccine coverage and effectiveness against medically attended laboratory‐confirmed influenza for the 2012 season. Design, setting and participants: Test‐negative design involving patients recruited as part of the Australian Sentinel Practices Research Network, a network of sentinel general practitioners throughout Australia. Throughout 2012, at the discretion of the GP at one of 102 participating practices, patients presenting with influenza‐like illness were swabbed and included in the study. Main outcome measure : Influenza vaccine effectiveness (VE) estimated as (1 − OR)*100% by logistic regression. Results: 1775 patients were swabbed. The epidemic period was identified as Weeks 10 to 43 of 2012. After exclusions, there were 1414 patients for the VE analysis, including 593 (42%) who tested influenza‐positive and 821 who tested negative. 27% of test‐negative patients were vaccinated, of whom most were aged 50 years and over. The overall VE, adjusted for age group, month of presentation and state or territory, was 23% (95% CI, − 4% to 43%) against all influenza types, 15% (95% CI, − 17% to 38%) against influenza A, 13% (95% CI, − 20% to 36%) against influenza A(not H1) and 53% (95% CI, 5% to 77%) against influenza B. Conclusion: Vaccination against influenza was modestly protective, reducing the risk of medical presentation with influenza by around 23%.